Preparation of reduced graphene oxide film by chemical and thermal reduction method targeted for energy harvesting - Ismail, Ili Nadia (2017)
Graphene has been the center of attraction for the past few years, all due to the unique and extraordinary characteristics of graphene. Tremendous researches have been done on various component of interest to discover the potential of this wonder material. This includes graphene as new source of energy. One of graphene special characteristics is a good conductor, hence the reason of this research project. In recent years, there have been researches done on harvesting energy from air and water flow over graphene film. A water flow over graphene has been proved that it can generate energy approximately ~175W/m2 due to the actively charged ions present in the water. In order to harvest the energy, a good quality of graphene film with high electrical conductivity is desired. In this dissertation, two techniques were used to prepare reduced graphene oxide film that is through chemical and thermal reduction. Characterization by X-Ray Diffractometer, Fourier Transform Infrared Spectrocopy and Field Emission Scanning Electron Microscope as well as Current versus Voltage test was carried out on each sample to measure the ability of reduced graphene film to harvest energy. As a result, thermal reduction at 700°C has shown the highest conductivity when compared to reduction done at 300°C and reduction by ascorbic acid. The conductivity obtained from thermal reduction at 700°C was relatively higher at 56.39 S/m followed by reduction with ascorbic acid at 46.87 S/m. Referring to the results obtained, it was proven that the conductivity increases significantly when the temperature increase, thus for that reason, the reduced graphene oxide by thermal reduction at higher temperature was suggested for energy harvesting purposes.